The Formation of PPMEâs Religious Identity - Sujadi, S. (Al-Jamiah: Journal of Islamic Studies, 2013)
The Persatuan Pemuda Muslim se-Eropa (PPME, Young Muslim Association in Europe) with its diverse religious backgrounds was established by many Indonesians living in the Netherlands. The organisation takes consideration not only the development of religious practices in Indonesia, but also the prevailing condition in the Netherlands in dealing its religious identity formation. The article focuses on how the organisationâs religious identitiy has been shaped. To deal with this issue, a historical approach is used, combining chronological presentation with analytical approach. This approach is in line with the objective of this research, i.e. to see the ways in which the PPMEâs religious identity take shape through reading the bulletins and religious practices. Because of its residence in the Netherlands, the shaping of its religious identity has been dictated by neither political force nor agenda. This led to in acceptance of diverse and plural ideas within the organisation. This has entailed the occurrence of diverse religious identities. Adjustments to the Dutch contexts have been featured by PPME. As a consequence, memories of Indonesia have been adapted to the atmosphere of the Netherlands.[Persatuan Pemuda Muslim se-Eropa (PPME) dengan keragaman latar belakang orientasi keagamaan anggotanya adalah organisasi yang didirikan oleh orang-orang Islam Indonesia yang tinggal di Belanda. PPME memperhatikan tidak saja keberagamaan ala Indonesia, namun juga kondisi di Belanda, utamanya dalam menegaskan identitas keberagamaan mereka. Artikel ini menjelaskan bagaimana identitas keagamaan PPME tersebut dibentuk. Untuk mendiskusikan tema tersebut, digunakan pendekatan sejarah --pendekatan yang tidak hanya menyajikan hasil penelitian secara kronologis tetapi juga eksplanasi analitis. Pendekatan ini sejalan dengan tujuan penulisan artikel ini, yaitu mengidentifikasi metode pembentukan identitas keagamaan PPME. Hal ini dilakukan dengan mencermati bulletin yang diterbitkan PPME dan aktifitas keagamaan yang dilaksanakan. Karena hidup di Belanda, identitas keberagamaan PPME berjalan dengan alamiah, tanpa intervensi politik. Ini mengakibatkan pada penerimaan PPME terhadap keragaman cara pandang yang hidup dalam PPME. Yang terakhir, PPME berusaha keras untuk menyesuaikan identitas keberagamaan mereka dengan konteks Belanda. Konsekuensinya, memori tentang Indonesia itu akhirnya diadaptasi dengan situasi dan kondisi di Belanda.]